TOOL WEAR OF (AL, CR, W) N-COATINGS ON CEMENTED CARBIDE TOOLS PREPARED BY ARC ION PLATING IN DRY CUTTING OF SINTERED STEEL: Received: 20th November 2022; Revised: 07th April 2023, 17th June 2023; Accepted: 14th July 2023 - Wada, Tadahiro (MATTER: International Journal of Science and Technology, 2023)
To improve both the critical scratch load and micro-hardness of (Al, Cr) N coating film, (Al, Cr, W) N coating film was developed. In this study, to clarify the tool wear of the coated tool in the cutting of sintered steel using four types of (Al, Cr, W) N coated tools, the wear progress and the wear mechanism of the coating film were investigated. By using two types of the (Al, Cr, W)-target and three types of bias voltage, the (Al, Cr, W) N coating film was deposited on cemented carbide ISO K10. To clarify the wear mechanism of the (Al, Cr, W) N coating films, scanning electron microscope (SEM) observation and Energy Dispersive X-ray spectrometry (EDS) mapping analysis of the abraded coating film were performed. The cutting conditions were a cutting speed of 3.33 m/s, feed rate of 0.1 mm/rev, and cutting depth of 0.1 mm. The following results were obtained: (1) The wear progress of the (Al64, Cr28, W8) N coated tool was slower than that of the (Al60, Cr25, W15) N coated tool. (2) When nitride coating films were deposited on the cemented carbide ISO K10 with a bias voltage of -80 V, -150 V, or -300 V using the (Al64, Cr28, W8)-target, the wear progress of the (Al64, Cr28, W8) N coated tool with a bias voltage of -80 V was the slowest.